On the distance and structure of W80 - Cersósimo, Juan Carlos (2007)
The continuum radiation of the Galactic region located at l = 85°, b = -0.5° is well defined by its 11 cm emission. The region, extended 3° in diameter, is cataloged as W80, and its optical images show the North America and Pelican Nebulae complexes. In this paper we present new distance measurements and physical parameters obtained from radio recombination line observations at a frequency near 1.4 GHz. Four structures are identified in the region under study: a near structure is located at a distance of about 0.7 kpc, another structure lies on the east side of W80 at a distance of 1.7 kpc, there is a concentration of ionized gas on the west side at a distance of 2.7 kpc, and a fourth structure is found further away at 3.3 kpc, which does not seem to belong to the W80 complex. The results are presented using the (X, Y, Z)-coordinates of the Galactic plane. The model used assumes a constant electron temperature Te = 6800 K and also assumes homogeneity. Our results seem to indicate that the ionized hydrogen of W80 spreads along the line of sight instead of clumping at one distance. We obtain values of the electron density and the ionization parameter between ne = 5 and 16 cm-3 and U = 51 and 110 cm-2 pc, respectively.